2015
DOI: 10.1038/ijo.2015.156
|View full text |Cite
|
Sign up to set email alerts
|

LAP-BAND for BMI 30–40: 5-year health outcomes from the multicenter pivotal study

Abstract: The LBS is safe and effective for people with BMI 30-39.9 with demonstrated improvements in weight loss, comorbidities and quality of life, and with a low explant rate through 5 years following treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 50 publications
3
15
0
Order By: Relevance
“…Improvement in general well-being is observed as early as 3 to 6 months after surgery [31,34,35]. While an initial increase in quality of life with a decrease in bodily pain is reported in the first year after surgery, contradictory observations are made in the few studies on larger cohorts of patients with specification of the pain location.…”
Section: Discussionmentioning
confidence: 88%
“…Improvement in general well-being is observed as early as 3 to 6 months after surgery [31,34,35]. While an initial increase in quality of life with a decrease in bodily pain is reported in the first year after surgery, contradictory observations are made in the few studies on larger cohorts of patients with specification of the pain location.…”
Section: Discussionmentioning
confidence: 88%
“…On February 16, 2011, the FDA granted approval for an extension of the indication to lower the BMI cutoff to 30 kg/m 2 in individuals with an obesity‐associated comorbid condition. The full 5‐year follow‐up of this lower‐BMI study cohort showed durable weight loss in association with improvement in patient‐reported outcomes, comorbidity change, and a much lower band explant rate of 12.1% compared with the historic 39.4%.…”
Section: Introductionmentioning
confidence: 76%
“…This study confirmed the extensive literature indicating clinically important improvement in quality of life following LBS surgery. The most significant and reproducible effect was the sustained community normalization of generic quality of life scores of the SF‐12 and the SF‐36 in cohorts having clearly impaired physical and mental summary scores at baseline . The Swedish Obese Subjects study demonstrated sustained benefit at 10 years .…”
Section: Discussionmentioning
confidence: 93%
“…Nevertheless, a clear improvement in psychological symptoms was found following surgery. Eleven out of 12 studies Crémieux et al 2010;Petasne Nijamkin et al 2013;Hayden et al 2014;Dixon et al 2003Dixon et al , 2015Dixon et al , 2016Morseth et al 2015;Gade et al 2015;Booth et al 2015;Sockalingam et al 2015;White et al 2015) demonstrated an improvement of depressive disorder both, with regard to prevalence and symptoms. The majority of the studies comprised a postoperative observation period that was not longer than three years.…”
Section: Depression and Anxiety Disordersmentioning
confidence: 99%